The Effectiveness Of Acupuncture In Improving Gait Function Among Elderly And Neurological Patients: A Systematic Review - Anggraini, Devanty (Syntax Corporation, 2025)
Gait, or walking pattern, is influenced by age, health condition, and neuromuscular function. Aging often leads to reduced walking speed, stability, and symmetry, which increases the risk of falls and decreases quality of life. Acupuncture, based on traditional meridian theory, has been investigated as a complementary intervention to improve gait function. This study is a systematic review conducted under PRISMA guidelines. Literature searches were performed in PubMed, Cochrane Library, Embase, and Scopus using keywords related to acupuncture and gait. Inclusion criteria were experimental studies on humans with acupuncture point stimulation, while studies on animals and those without details of acupuncture points were excluded. The results suggest that acupuncture may improve walking speed, stride length, and cadence. Positive effects were observed in older adults and patients with neurological disorders. Proposed mechanisms include modulation of the nervous system and connective tissue interactions. However, heterogeneity in study design and acupuncture point selection limits the generalizability of findings. In conclusion, acupuncture shows potential as a complementary therapy to enhance gait function in aging and neurological conditions, although larger standardized clinical trials are still needed.